Erratum: Proton and Hydrogen Transport through Hydrogen Environments: Ionization and Stripping - Cariatore, Nelson Daniel (2022)
Corrected data is provided here for ionization in H+ + H for the laboratory collision energies between 50 and 10,000 keV regarding the integral and differential cross sections, as well as average values of kinematic parameters such as energy loss and projectile scattering angle...